Nilai Moral pada Novel “Alang” Karya Desi Puspitasari dan Implementasinya dalam Pembelajaran Sastra di SMA - Tusoleha, Wilda Amelia; Hikmat, Ade (GERAM, 2024)
The current condition of language and literature learning is still not optimal. Therefore, the researcher conducted a study to examine moral values and their application in student learning in high school through the novel "Alang" by Desi Puspitasari. Thus, it is expected that students can understand various moral values conveyed through the activities of characters in everyday life. The novel "Alang" by Desi Puspitasari has many lessons, including moral values. In this novel, it is explained how moral values are conveyed through the activities of characters who have various morals. As a work of fiction, this novel describes the journey of human life as a whole and provides teachings about true human behavior, as well as providing direction on the values of good and bad that become guidelines in social life. The subfocus in this study is the form of moral values that contain human relationships with themselves, moral values that contain human relationships with humans, moral values that contain human relationships with nature, moral values that contain human relationships with God in the Novel "Alang" by Desi Puspitasari.